The Arabidopsis acetylated histone-binding protein BRAT1 forms a complex with BRP1 and prevents transcriptional silencing - Cui-Jun Zhang; Xiao-Mei Hou; Lian-Mei Tan; Chang-Rong Shao; Huan-Wei Huang; Yong-Qiang Li; Lin Li; Tao Cai; She Chen; Xin-Jian He (Nature Communications, 2016)
Transposons and repetitive sequences are typically subject to transcription silencing. Here, Zhang et al. find that the bromodomain-containing protein BRAT1 forms a complex with BRP1, recognizes histone acetylation and acts to prevent transcriptional silencing in Arabidopsis.